2022
DOI: 10.1017/psrm.2022.45
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the relative influence of party unity on vote choice: evidence from a conjoint experiment

Abstract: Observational studies and anecdotal evidence suggest that party unity improves a party's electoral performance. Yet, due to a lack of experimental evidence, the causal standing of these findings remains unclear. Moreover, party unity manifests in various ways and we do not know how much different types of party unity affect the vote. Relying on a conjoint experiment implemented in a probability-based survey of the German population, our study unveils the distinct causal effect of different forms of party unity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…As Michels (1911) argues, a high level of intra-party competition can not only weaken party unity but also the chances of the party in the electoral contest (see also e.g. Greene and Haber, 2015;Lehrer et al, 2022). Therefore, it can be assumed that parties strive to reduce intensity of intra-party competition since candidate selection takes place shortly before the election campaign and the elections.…”
Section: Theoretical Framework: Informal Rules and Competing Logics O...mentioning
confidence: 99%
“…As Michels (1911) argues, a high level of intra-party competition can not only weaken party unity but also the chances of the party in the electoral contest (see also e.g. Greene and Haber, 2015;Lehrer et al, 2022). Therefore, it can be assumed that parties strive to reduce intensity of intra-party competition since candidate selection takes place shortly before the election campaign and the elections.…”
Section: Theoretical Framework: Informal Rules and Competing Logics O...mentioning
confidence: 99%
“…Electoral research has shown that voters indeed react to MPs' legislative behaviour (Papp and Russo, 2018;Wagner et al, 2020;Duell et al, 2023). Disunity as a negative valence signal endangers the party's issue ownership and, for government parties, their policy-making capability and will ultimately be punished by voters (Greene and Haber, 2015;Lehrer et al, 2022). Accordingly, the party group leadership is inclined to use the whip to a stronger extent during consequential and salient votes in order to prevent harm to the party (Owens, 2003).…”
Section: Theorymentioning
confidence: 99%
“…Party unity is thus considered a precondition for responsible party government (Bowler et al, 1999). A lack of party unity is punished at the ballot box (Lehrer et al, 2022) and, on the member of parliament (MP) level, with lower chances of career advancement (Schobess and de Vet, 2022). Moreover, hypotheses on the formation of minimal winning coalitions would be meaningless if parties could not rely on the support of all their MPs.…”
Section: Introductionmentioning
confidence: 99%